Pengaruh Kemampuan Berpikir Kritis Siswa melalui Model Pembelajaran Student Facilitator and Explaining Berbantu Media Audiovisual pada Pembelajaran Bahasa Indonesia bagi Siswa Kelas IV SDN Mayonglor 04 Jepara - Rifdah Rifdah; Ika Ari Pratiwi; Much Arsyad Fardani (ISLAMIKA, 2023)
This study aims to analyze the influence and improvement of students' critical thinking skills before and after using the Student Facilitator and Explaining learning model assisted by audiovisual media in learning Indonesian for Grade IV students at SDN Mayonglor 04 Jepara. This study used a quantitative experimental research design, namely Quasi Experimental with the Nonequivalent Control Group Design model. Data obtained through observation, learning evaluation, test instruments, questionnaires and documentation. The location of this research will be carried out in class IV SDN Mayong 04 Jepara. The sample in this study were all students of class IV A & B at SDN Mayonglor 04, totaling 38 students using a random sampling technique. The results of this study show the score of the Independent Samples Test with a sig. (2 tailed) of 0.000 <0.05, then there is a difference in the average critical thinking ability of students in the control class (68.50) which uses conventional learning and the experimental class (82.60) which uses the Student Facilitator and Explaining model assisted by media audio visual. Whereas from the N-gain test the score for the experimental class was 63.2416 or 63% and for the control class 32.6714 or 33% which can be interpreted that the use of the Student Facilitator and Explaining model assisted by audiovisual media in the experimental class is quite effective in increasing critical thinking skills students in Indonesian content.